Attentional Competition and Semantic Integration in Low- and High-Span Readers - Guan, Connie Qun; Fraundorf, Scott H.; Gao, Mingle; Zhang, Chong; MacWhinney, Brian (Frontiers in Psychology, 2022)
The goal of the current study is to investigate the effects of the distractive textual information on the activation of predictive inference online, and how the readers with high or low working memory capacity differ in their online activation and text memory. To test the two hypothesis of attentional competition and semantic integration, we conducted three experiments to investigate whether a local prediction (e.g., “The vase broke”) and a global prediction (e.g., “The wife left her husband”), both of which could be derived from the description of a critical event (e.g., “The angry husband throws the delicate porcelain vase against the brick wall”), are generated in the mind of the reader, and how this generation process is influenced by contextual and cognitive factors of the reader (e.g., working memory capacity). The results of Experiment 1 and 2 suggest that the elaboration of the global aspects in the narrative reduces the local prediction, but makes the global prediction more salient to occur. The evidence from Experiment 3 confirms the hypothesis that even automatic processes are constrained by distant contextual factors, in combination with differences in working memory, and examines how referentially local and global predictions are intertwined in text comprehension. Overall, these data support the immediate integration hypothesis across sentence boundaries at different representation levels (cf. Schmalhofer & Perfetti, 2007), as well as interaction assumptions of different processing levels within referentially local and referentially global processing contexts (cf. Yang, Perfetti, & Schmalhofer, 2007).